Peningkatan Layanan Teknologi Informasi Digital Marketing pada Beryl Foam Purbalingga Menggunakan Framework ITIL V4 - Rizky Gilang Setiawan; Hermawan Hermawan; Faikul Farid; Taufik Nur Hidayat; Ito Setiawan (JOURNAL SAINS STUDENT RESEARCH, 2026)
The improvement of digital marketing information technology services at Beryl Foam Purbalingga is carried out using the ITIL V4 framework. Digital marketing services are utilized through Instagram social media and the Shopee e-commerce platform; however, their management remains unstructured and reactive. This study applies a qualitative descriptive method with a case study approach through observation and interviews. The analysis is based on the Service Value System (SVS), the four dimensions of ITIL V4 service management, and relevant ITIL V4 practices, including incident management, service request management, and continual improvement. The results indicate that digital marketing IT services have not fully created business value due to the absence of structured service procedures and planned evaluations. Therefore, the implementation of simple service procedures, the application of the focus on value principle, and continuous improvement are recommended to enhance digital marketing IT services and support UMKM business objectives.